Isolation of the Lateral Border Recycling Compartment Using a Diaminobenzidine‐Induced Density Shift. (1st July 2014) - Sullivan, David P.; Rüffer, Claas; Muller, William A.
<x xml:space="preserve">Abstract</x> The migration of leukocytes across the endothelium and into tissue is critical to mounting an inflammatory response. The lateral border recycling compartment (LBRC), a complex vesicular‐tubule invagination of the plasma membrane found at endothelial cell borders, plays an important role in this process. Although a few proteins have been shown to be present in the LBRC, no unique marker is known. Here, we detail methods that can be used to characterize a subcellular compartment that lacks an identifying marker. Initial characterization of the LBRC was performed using standard subcellular fractionation with sucrose gradients and took advantage of the observation that the compartment migrated at a lower density than other membrane compartments. To isolate larger quantities of the compartment, we modified a classic technique known as a diaminobenzidine (DAB)‐induced density shift. The DAB‐induced density shift allowed for specific isolation of membranes labeled with horseradish peroxidase‐conjugated antibody. Because the LBRC could be differentially labeled at 4°C and 37°C, we were able to identify proteins that are enriched in the compartment, despite lacking a unique marker. These methods serve as a model to others studying poorly characterized compartments and organelles and are applicable to a wide variety of biological systems. <inline-graphic xlink:href="ark:/27927/pgh11r1h58t" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />